Study Abroad Push Causes and Their Impact on Educational Institutions: A Case Study of Nepal - Bhanu Bhakta Pokharel; Dr. Vijesh Kumar; Daman Bahadur Singh; Basudev Lamichanne (Journal of Development Review, 2025)
This study looks at why Nepali students choose to pursue their education overseas and its impact on education in Nepal, society, and the economy. A systematic review was conducted to examine the literature further using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) criteria. After going through the inclusion and exclusion criteria, publications on student migration from Nepal, brain drain, and socioeconomic impacts between [2015 to 2023] were collected from electronic databases. of these, [27] articles were ultimately used. Then, data on issues such as a lack of educational possibilities, political unpredictability, financial restrictions, and the belief that professional chances are better abroad were extracted and analyzed using thematic analysis. The results showed that studying overseas has significantly reduced Nepal's brain drain, which had a detrimental impact on the country's technological, healthcare, and educational systems in addition to creating social and economic issues. Thus, to reduce student departure and retain talent in Nepal, this study ends with recommendations for raising the standard of higher education there.